Comparison of absolute and relative handgrip strength to predict cancer prognosis: A prospective multicenter cohort study. Issue 8 (August 2022) - Xie, Hailun; Ruan, Guotian; Deng, Li; Zhang, Heyang; Ge, Yizhong; Zhang, Qi; Lin, Shiqi; Song, Mengmeng; Zhang, Xi; Liu, Xiaoyue; Li, Xiangrui; Zhang, Kangping; et al.
Summary: Background & aims: Decreased muscle strength, as measured by absolute handgrip strength (HGS), is associated with poor outcomes in patients with cancer. The ability of HGS to predict cancer prognosis may be affected by its absolute or relative representation. It is not clear whether absolute or relative HGS is more appropriate for the prognostic assessment of cancer. Methods: We conducted a multicenter prospective cohort study of 16, 150 cancer patients. The exposure variables were absolute and relative HGS values. Relative HGS was standardized according to height, weight, body mass index (BMI), and mid-arm circumference (MAC). The Cox proportional hazard regression model was used to determine the relationship between HGS-related indices and survival. Logistic regression analysis was used to assess the association between HGS-related indices and 90–day outcomes. Results: Both absolute and relative HGS were independent prognostic factors for cancer. All HGS-related indices are applicable to lung and colorectal cancer. Both absolute and MAC-adjusted HGS are applicable for breast cancer. For the prognostic assessment of hepatobiliary and urologic cancers, only height-adjusted HGS is applicable. Compared with absolute HGS, height-adjusted HGS had a better prediction performance (0.007; 95% CI, 0.006, 0.008; log-rank P < 0.001), particularly in lung and colorectal cancer. However, the prediction performance of weight/BMI/MAC-adjusted HGS was worse than that of absolute HGS by (−0.015; 95% CI, −0.020, −0.011; log-rank P < 0.001), (−0.028; 95% CI, −0.033, −0.023; log-rank P < 0.001), and (−0.019; 95% CI, −0.022, −0.016; log-rank P < 0.001), respectively. Low absolute and relative HGS were significantly associated with poor 90–day outcomes in patients with cancer. Height-adjusted HGS was better than absolute HGS in predicting 90–day outcomes, particularly in lung cancer. Conclusion: Among the HGS-related indices, height-adjusted HGS has an optimal value in predicting the short- and long-term survival of cancer patients, especially those with lung cancer.